(untitled) - Boissonnat, J.-D. (Cambridge, United Kingdom,New York, 1998)
The design and analysis of geometric algorithms has seen remarkable growth in recent years, due to their application in computer vision, graphics, medical imaging, and CAD. Geometric algorithms are built on three pillars: geometric data structures, algorithmic data structuring techniques and results from combinatorial geometry. This comprehensive presents a coherent and systematic treatment of the foundations and gives simple, practical algorithmic solutions to problems. An accessible approach to the subject, Algorithmic Geometry is an ideal guide for instructors or for beginning graduate courses in computational geometry
Keywords: Algorithms,Hình học,Thuật toán,Geometry; Xử lý dữ liệu,Data processing